The Hagiographic Image of the Saintly Dorothy Barzi — Creating Personal Patterns in the Adam Makowski’s Sermon The Annual and Perennial Reminder (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The object of the presentation is not another attempt to reconstruct a biography, but an analysis ofthe image praise created by Father Adam Makowski. The image that has been created in the form of oratory.The author is respecting the rules of constructioning anniversary sermons. Convention exploits inorder to make a monument for the dead, which has been created for herself, living piously fulfilling theworks of mercy and materially supporting the Jesuits and the poor. The title of oration seems to indicatesuch an intention by the writer: The Annual and Perennial Reminder [...] Dorothy of Ojźrzaków Barzina[...] at the Memorial Service Offered. Literary imagery requires the overview in the light of hagiographicwriting conventions. This is all the more necessary that Dorothy Barzi was describing as saintly, the pious,holy.This article presents an outline of a biographical figure, analysis of the structure of the sermon. Thearticle juxtaposes conventions of funeral preaching and hagiographic text functions, and finally discussesthe elements of the hagiographic image of Dorothy Barzi. These elements are: the origin, marital status(adequately the praise of son acts), pious activities, taking on persecution, work for the Church, mortification(posts cilice), showing humility, concern for the Jesuits (donations), the poor (charity), the sickand imprisoned (care), setting a school for girls, pious death.